Biogenic synthesis of silver nanoparticles using nicotiana tobaccum leaf extract and study of their antibacterial effect - Prasad, Kumar Suranjit; Pathak, Darshit; Patel, Ankita; Dalwadi, Palak; Prasad, Ram; Patel, Pradip; Selvaraj, Kaliaperumal (African Journal of Biotechnology, 2011)
A green synthesis of silver nanoparticle was carried out using tobacco leaf extract. Synthesized nanoparticles were characterized using UV-Vis absorption spectroscopy, TEM, EDAX, FT-IR and photoluminescence study, respectively. UV-Vis absorption spectroscopy of prepared silver colloidal solution showed absorption maxima at 418 nm. Excitation maximum and emission maximum obtained from photoluminescence study were found at 414 and 576 nm, respectively. TEM analysis showed average particle size of 8 nm, while SAED pattern confirmed the crystalline nature of synthesized nanoparticles. FT-IR analysis indicated the involvement of carboxyl (-C = O), hydroxyl (-OH) and amine (-NH) functional groups of tobacco leaf extract in preparation of silver nanoparticles. EDAX analysis showed proportion of silver (54.55%) among other elements in nanoparticle. Pseudomonas aeruginosa and Escherichia coli DH5 alpha showed highest sensitivity towards silver nanoparticles.
Keywords: FT-IR spectroscopy; photoluminescence; silver nanoparticles; Tobacco; UV-Vis absorption

Biosynthesis of Se nanoparticles and its effect on UV-induced DNA damage - Prasad, Kumar Suranjit; Patel, Hirnee; Patel, Tirtha; Patel, Khusbu; Selvaraj, Kaliaperumal (Colloids and Surfaces B-Biointerfaces, 2013)
This paper reports, an environmentally benign procedure of synthesis and characterizations of selenium nanoparticles and their protective effect against UV-induced DNA damage activities. An aqueous leaf extract of lemon plant was used as a precursor for synthesis of colloidal selenium nanoparticles. Resulting nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX, FT-IR and XRD, respectively. Selenium colloidal solution exhibited an absorption maximum at 395 nm and produced an emission maximum at 525 nm. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, selenium nanoparticles of diameter ranging from (similar to 60 to 80 nm). X-ray diffraction studies showed the formation of 111, 2 0 0 and 220 planes of face-centered cubic (fcc) selenium. EDAX analysis confirmed the presence of selenium in nanosphere. Fourier transformed infrared spectroscopic investigation reveled the involvement of carboxyl (-C=0), hydroxyl (-OH), amine (-NH) functional group of lemon plant extract in preparation of selenium nano particles. MU assay as well single cell gel electrophoresis assay or comet assay revealed that synthesized selenium nanoparticles, caused less cell death of lymphocytes and prevented DNA damage, when cells were exposed to UVB. The fluorescent property of selenium nanopartides can be used as diagnostic agent. Further, their anti DNA damaging property can be investigated as a chemotherapeutic agent in cancer therapy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Comet assay; EDAX; FT-IR; MTT assay; Selenium nanoparticles; UV-vis spectrophotometer

Biogenic synthesis of selenium nanoparticles and their effect on as(III)-induced toxicity on human lymphocytes - Prasad, Kumar Suranjit; Selvaraj, Kaliaperumal (Biological Trace Element Research, 2014)
{A bioreductive capacity of a plant, Terminalia arjuna leaf extract, was utilized for preparation of selenium nanoparticles. The leaf extract worked as good capping as well as stabilizing agent and facilitated the formation of stable colloidal nanoparticles. Resulting nanoparticles were characterized using UV-Vis spectrophotometer, transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction analysis (XRD), respectively. The colloidal solution showed the absorption maximum at 390 nm while TEM and selected area electron diffraction (SAED) indicated the formation of polydispersed, crystalline selenium nanoparticles of size raging from 10 to 80 nm. FT-IR analysis suggested the involvement of O-H, N-H
Keywords: Arsenite; Comet assay; EDAX; MTT assay; Selenium nanoparticles; Terminalia arjuna

Bioresponsive carbon nano-gated multifunctional mesoporous silica for cancer theranostics - Prasad, Rajendra; Aiyer, Sandhya; Chauhan, Deepak S.; Srivastava, Rohit; Selvaraj, Kaliaperumal (Nanoscale, 2016)
Designing bioresponsive nanocarriers for controlled and efficient intracellular drug release for cancer therapy is a major thrust area in nanomedicine. With recent recognition by the US FDA as a safe material for human trials, mesoporous silica nanoparticles (MSNPs) are being extensively explored as promising theranostic agents. Green fluorescent carbon quantum dots (CQDs), though known as possible alternatives for their more toxic and relatively less efficient predecessors, are less known as gate keepers for drug release control. We report for the first time an efficient bioresponse of CQDs when judiciously designed using glutathione cleavable (redox responsive) disulphide bonds. When the anticancer drug doxorubicin loaded MSNPs are capped with these CQDs, they display promising drug release control on exposure to a mimicked intracellular cancer environment. Their dual functionality is well established with good control on preventing the premature release and exceptional bio-imaging of HeLa cancer cells. Fluorescence images prove selective targeting of HeLa cells by overexpression of folate receptors from the surface functionalised folic acid ligand. Extensive characterisation using XRD, TEM, BET analysis, drug loading tests, drug release kinetics, MTT assay and fluoroscence cell imaging helps in understanding the multi-functionalities of the successful design, extending its scope with exciting prospects towards non-invasive targeted drug delivery and bio-imaging for effective cancer diagnosis and treatment.